Clinical significance of exosomal noncoding RNAs in hepatocellular carcinoma: a narrative review - Jae Sung Yoo; Min Kyu Kang (Journal of Yeungnam Medical Science)
Hepatocellular carcinoma (HCC) is one of the most lethal malignancies worldwide, with poor prognosis owing to its high frequency of recurrence and metastasis. Moreover, most patients are diagnosed at an advanced stage owing to a lack of early detection markers. Exosomes, which are characterized by their cargos of stable intracellular messengers, such as DNA, RNA, proteins, and lipids, play a crucial role in regulating cell differentiation and HCC development. Recently, exosomal noncoding RNAs (ncRNAs), including microRNAs, long ncRNAs, and circular RNAs, have become increasingly important diagnostic, prognostic, and predictive markers of HCC. Herein, we discuss the clinical implications of exosomal ncRNAs, specifically those within the HCC regulatory network.